1995
DOI: 10.1002/food.19950390503
|View full text |Cite
|
Sign up to set email alerts
|

Trans fatty acids: Implications for health, analytical methods, incidence in edible fats and intake

Abstract: Trans fatty acids (TFA) are supposed to be related to a variety of physiological effects. Numerous studies in this field are gathered and compared, which mainly deal with the influences on lipoprotein levels in plasma and their effects with regard to coronary heart diseases. Furthermore, the analytical accessibility of trans fatty acids by different methods is presented. Thus, the most reliable method for an exact quantitation of trans fatty acids in edible fats is the combination of Ag-TLC with GC. The conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
86
0
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(92 citation statements)
references
References 132 publications
4
86
0
2
Order By: Relevance
“…Weiland et al (1999) found in an ecological study that the intake of transfatty acids is associated with allergic disease. It was suggested that trans-fatty acids promotes an increase in IgE production, mediated by the modulation of the desaturation and chain elongation of n-6 and n-3 fatty acids, thereby influencing the prostaglandin and leukotrienes synthesis (Precht and Molkentin, 1995). We did not find an association between asthma and dietary intake of the n-3 PUFA, a-linolenic acid (C18:3), eicosapentaenoic acid (EPA, C20:5) and docosahexaenoic acid (DHA, C22:6), whereas an inverse relationship between eicosapentaenoic acid (EPA, C20:5) intake and hay fever risk in adults in a recent study in the EPIC-Heidelberg cohort was observed (Nagel et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Weiland et al (1999) found in an ecological study that the intake of transfatty acids is associated with allergic disease. It was suggested that trans-fatty acids promotes an increase in IgE production, mediated by the modulation of the desaturation and chain elongation of n-6 and n-3 fatty acids, thereby influencing the prostaglandin and leukotrienes synthesis (Precht and Molkentin, 1995). We did not find an association between asthma and dietary intake of the n-3 PUFA, a-linolenic acid (C18:3), eicosapentaenoic acid (EPA, C20:5) and docosahexaenoic acid (DHA, C22:6), whereas an inverse relationship between eicosapentaenoic acid (EPA, C20:5) intake and hay fever risk in adults in a recent study in the EPIC-Heidelberg cohort was observed (Nagel et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogenated fats are widely used in food products as a substitute for saturated fats (eg margarines, shortenings and frying fats). Estimates of intake during recent decades have varied between 2.6 and 12.8 gaday in the USA and between 2.0 and 17.4 gaday in Europe (Precht & Molkentin, 1995;Becker, 1996;Special Task Force, 1996;Allison et al, 1999), with the lowest estimates obtained from food frequency questionnaires.…”
Section: Introductionmentioning
confidence: 99%
“…Given the physiological effects of other fatty acids for which TFAs might be a substitute, this evaluation should include the relation of TFA intake with intake of other fatty acids, particularly that of the saturated fatty acids. Estimates of TFA intake vary between 8.1 and 12.8 gaday in the United States, and between 2.4 and 17.4 gaday in Europe (Boatella et al, 1993;Precht & Molkentin, 1995;Becker 1996). Differences in estimates can be attributed partly to differences in food consumption data used and lack of information on actual TFA content of foods.…”
Section: Introductionmentioning
confidence: 99%